2022
DOI: 10.3389/fonc.2022.772405
|View full text |Cite
|
Sign up to set email alerts
|

The Polymorphism and Expression of EGFL7 and miR-126 Are Associated With NSCLC Susceptibility

Abstract: Previous investigations have reported that microRNA-126 (miR-126) and its host gene, epidermal growth factor-like domain-containing protein 7 (EGFL7) are involved in lung cancer progression, suggesting EGFL7 and miR-126 play a joint role in lung cancer development. In this study, we analyzed the methylation-associated regulation of EGFL7 and miR-126 in non-small cell lung cancer (NSCLC) and further investigated the association between EGFL7/miR-126 polymorphisms and NSCLC susceptibility in the Han Chinese popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“… 42 Liu et al have found that EGFL7/miR-126 polymorphism rs2297538 was associated with the risk of non-small cell lung cancer. 43 In addition, Yu et al have identified a novel regQTL-SNP, rs3768617, may have effects on lung cancer risk by influencing the expression of miRNA-548b-3p and LAMC1. 44 These studies remind us that we could also explore the association between SNPs in cuproptosis-related lncRNA, miRNA and lung cancer risk, and might identify some novel regQTL-SNP related to lung cancer risk in further studies.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Liu et al have found that EGFL7/miR-126 polymorphism rs2297538 was associated with the risk of non-small cell lung cancer. 43 In addition, Yu et al have identified a novel regQTL-SNP, rs3768617, may have effects on lung cancer risk by influencing the expression of miRNA-548b-3p and LAMC1. 44 These studies remind us that we could also explore the association between SNPs in cuproptosis-related lncRNA, miRNA and lung cancer risk, and might identify some novel regQTL-SNP related to lung cancer risk in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that it could serve as a diagnostic factor due to a significant decrease in its expression in advanced-stage NSCLC compared to the early-stage NSCLC cases [ 41 ]. It was found to be strongly downregulated in the NSCLC [ 40 ] cell lines [ 27 , 75 , 76 ], tissues [ 27 , 74 , 75 , 76 ], body fluids [ 74 ], and serum-derived exosomes [ 73 ]. An increase in its expression supresses the aggressiveness of the tumour cells through various pathways [ 27 , 40 , 74 , 75 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The expression of miR‐126 and EGFL7 in NSCLC can be concomitantly downregulated through methylation of CpG islands, thereby inhibiting NSCLC cell proliferation and tumor growth. A recent study observed that EGFL7 and miR‐126 are associated with the risk of NSCLC in the Han Chinese population (Liu et al, 2022).…”
Section: Egfl7 Expression In Tumorsmentioning
confidence: 99%